Specific Immune Response and Cytokine Production in CD70 Deficiency - Abolhassani, Hassan (Frontiers in Pediatrics, 2021)
Collective clinical and immunologic findings of defects in the CD27-CD70 axis indicate a primary immunodeficiency associated with terminal B-cell development defect and immune dysregulation leading to autoimmunity, uncontrolled viral infection and lymphoma. Since the molecular mechanism underlying this entity of primary immunodeficiency has been recently described, more insight regarding the function and profile of immunity is required. Therefore, this study aimed to investigate stimulated antibody production, poly-clonal versus virus-specific T-cell response and cytokine production of a CD70 deficient patient-reported previously with early-onset antibody deficiency suffering from chronic viral infections and B-cell lymphoma. The patient and her family members were subjected to clinical evaluation, immunological assays and functional analyses. The findings of this study indicate an impaired ability of B cells to produce immunoglobulins and a poor effector function of T-cells was also associated with the severity of clinical phenotype. Reduced proportions of cells expressing the memory marker CD45RO, as well as T-bet and Eomes were observed in the CD70 deficient T cells. the proportion of 2B4+ and PD-1+ virus-specific CD8+ T-cells was also reduced in the patients. Although the CD70 mutated individuals presented with early-onset clinical manifestations that were well controlled by using conventional immunological and anti-cancer chemotherapies, with better prognosis as compared to CD27 deficient patients, targeted treatment toward specific disturbed immune profile may improve the management and even prevent secondary complications.